Northern bobwhite population responses to winter weather along their northern range periphery - Adam K. Janke; Theron M. Terhune; Robert J. Gates; C. Robert Long (Wildlife Society Bulletin)
ABSTRACT Relationships between northern bobwhite (Colinus virginianus) population dynamics and weather are well‐established and managed in the southern and western core of their range. Although a qualitative recognition of effects of winter weather at the northern edge of the northern bobwhite range exists, quantitative evaluations that examine impacts of severe winter weather events on declining northern populations are lacking. We used radiotelemetry to evaluate relationships between daily survival and winter weather in 2 northern populations in Maryland and Ohio, USA. Ninety‐day winter (Dec–Feb) survival varied with total snow accumulation among years and sites, with lowest survival (0.007, SE = 0.007) occurring during greatest snow accumulation and highest survival (0.498, SE = 0.088) during the mildest winter. Snow depths were negatively associated with daily survival in Ohio and Maryland, whereas association with temperature was marginal and differed among sites and years. We used northern bobwhite counts from the North American Breeding Bird Survey (NABBS) to test whether local effects of snow accumulation on winter survival manifest in population reductions up to 5 years following locally extreme snow accumulation events on 128 routes in the northern bobwhite range. Our best‐supported linear mixed model showed snow accumulation during 4 preceding winters was associated with population declines, with declining associations between abundance and snow accumulation over longer time lags. Our NABBS analysis linked local demographic effects from the radiotelemetry study to population‐level changes in abundance at a wide geographic scale, collectively illustrating the capacity for comparatively rare but severe winter weather events to produce a legacy of population change among northern populations. Conservation strategies for these populations should take into account the potential effect of severe winter weather on population stability and seek to employ conservation measures that increase resiliency to severe winter weather events. © 2017 The Wildlife Society.